2020
DOI: 10.3389/fchem.2020.590191
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Ionic Liquid/Metal Organic Framework Composites for CO2/CH4 and CO2/N2 Separations

Abstract: Global warming is arguably the biggest scientific challenge of the twenty-first century and its environmental consequences are already noticeable. To mitigate the emissions of greenhouse gases, particularly of CO 2 , there is an urgent need to design materials with improved adsorbent properties. Five different magnetic ionic liquids were impregnated into the metal–organic framework ZIF-8. The composites were produced by a direct-contact method, and their performance as sorbents for gas s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…Although the reported equilibrium selectivity did not take into account the influence of adsorption kinetics or the impact of a real gas mixture, these results serve as a first evaluation of the good potential of Zn(dcpa) for CO2 separation from CO2/N2 and CO2/CH4 mixtures. Comparing the selectivity of Zn(dcpa) for CO2/N2 with those of the commercial MOFs MIL-53(Al) [31], ZIF-8, [44], and Fe-BTC [45] (Figure 10b,c), it is concluded that the former outperformed the others at a lower pressure. For example, at 1 bar, the order of selectivities was 12.8 (Zn(dcpa)) > 10.5 (Fe-BTC) > 9.6 (MIL-53(Al)) > 5.9 (ZIF-8).…”
Section: Potential Of Zn(dcpa) For Co2/n2 and Co2/ch4 Separationmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the reported equilibrium selectivity did not take into account the influence of adsorption kinetics or the impact of a real gas mixture, these results serve as a first evaluation of the good potential of Zn(dcpa) for CO2 separation from CO2/N2 and CO2/CH4 mixtures. Comparing the selectivity of Zn(dcpa) for CO2/N2 with those of the commercial MOFs MIL-53(Al) [31], ZIF-8, [44], and Fe-BTC [45] (Figure 10b,c), it is concluded that the former outperformed the others at a lower pressure. For example, at 1 bar, the order of selectivities was 12.8 (Zn(dcpa)) > 10.5 (Fe-BTC) > 9.6 (MIL-53(Al)) > 5.9 (ZIF-8).…”
Section: Potential Of Zn(dcpa) For Co2/n2 and Co2/ch4 Separationmentioning
confidence: 98%
“…Figure 10. (a) Adsorption equilibrium isotherms of CO 2 ( ), CH 4 ( ), and N 2 (•) on Zn(dcpa) at 303 K. Filled and empty symbols represent adsorption and desorption data, respectively; (b) CO 2 /N 2 and (c) CO 2 /CH 4 equilibrium selectivity at 303 K as a function of pressure for Zn(dcpa) and commercial MOFs MIL-53(Al)[31], ZIF-8[44], and Fe-BTC[45].…”
mentioning
confidence: 99%
“…In this work, replicate measurements were done to check data reproducibility. Further details concerning the gravimetric apparatus and methodology employed in the measurements can be found elsewhere [13,[22][23][24].…”
Section: Gas Adsorption/desorption Equilibrium Measurementsmentioning
confidence: 99%
“…The other potential location of the IL consists of its successful encapsulation inside the cavity of the MOF. This strategy originated from attempts to improve MOF sorption properties [12,13,31,32]. Target molecules for separation from CO 2 (with a kinetic diameter of 3.3 A) include nitrogen (N 2 ; 3.64 A) and methane (CH 4 ; 3.8 A), and the functionalization of MOFs through ILs has allowed the preparation of more selective materials in terms of preferential sorption towards CO 2 [33,34].…”
Section: Introductionmentioning
confidence: 99%